Association Between Plasma Concentration Of Factor VIII Related Antigen, ABO Blood Type And Lewis Blood Type - Orstavik, K H; Magnus, P (Thrombosis and Haemostasis, 1981)
Individuals with blood type 0 have a lower plasma concentration of factor VIII than individuals with blood type A. Since the Lewis blood type system and the ABO blood type system are related, we looked for a possible association between the plasma concentration of factor VIII and Lewis blood type.Plasma concentration of factor VIII related antigen (FVIIIR:Ag) was determined by the Laurell electroimmunoassay in 333 individuals. These individuals were identical and fraternal twins who had been bled as part of a twin study on coagulation factors. The association between factor VIII and ABO blood type was confirmed since a significantly lower concentration of FVIIIR:Ag was found in individuals with blood type 0 (77%) than in individuals with blood type A (106%). Lewis blood type had no significant effect on the concentration of FVIIIR:Ag when the whole material was examined. Within individuals with blood type 0, a much lower concentration of FVIIIR:Ag was found in individuals with Lewis blood type Le(a-b-) (52%) compared to individuals with Lewis blood type Le(a-b+) (80%) or Le(a+b-) (88%).The possibility that individuals with blood type 0 and no Lewis antigens have a low plasma concentration of factor VIII may have implications for the detection of carriers of hemophilia A.